Finite-Time Bounded Model-Based Event-Triggered Control for Distributed Fuzzy T-S Systems - Davood Nazari Maryam Abadi; Ali Moarefianpour; Nima Mahdian Dehkordi (Majlesi Journal of Electrical Engineering, 2024)
In this paper, the problem of model-based finite-time bounded event-triggered control for distributed fuzzy T-S systems is presented. For this purpose, the whole network model is embedded locally in both the controller and the remote telemetry unit. In order to estimate the states of the plant between two consecutive events, a fuzzy observer has been used. Model-based state estimation reduces the state error and consequently leads to reduction of data transmission instants. By the network model and event triggering block which are placed locally in each remote telemetry unit, the time of data transmission on the distributed network is determined. Finally, the finite-time boundedness of the closed-loop system has been investigated using MATLAB software for a centralized and a distributed system, respectively.